Modulation of Major Histocompatibility Complex Protein Expression by Human Gamma Interferon Mediated by Cysteine Proteinase-Adhesin Polyproteins of Porphyromonas gingivalis - Yun, Peter L. W. (American Society for Microbiology, 1999)
Cysteine proteinases have been emphasized in the virulence of Porphyromonas gingivalis in chronic periodontitis. These hydrolases may promote the degradation of extracellular matrix proteins and disrupt components of the immune system. In this study it was shown that purified Arg-gingipain and Lys-gingipain inhibited expression of class II major histocompatibility complex (MHC) proteins in response to the stimulation of endothelial cells with human gamma interferon (IFN-γ). Treatment with the cysteine proteinases resulted in a rapid shift in the apparent molecular size of IFN-γ from 17 to 15 kDa, as shown by Western blot analysis, a response which also occurred in the presence of serum. Further, glycosylated natural IFN-γ from human leukocytes and unglycosylated recombinant IFN-γ from Escherichia coli were both digested by the cysteine proteinases. Immunoblot analysis indicated that cleavage within the carboxyl terminus of recombinant IFN-γ correlated with the loss of induction of MHC class II expression as monitored by analytical flow cytometry. No hydrolysis of MHC class II molecules or human IFN-γ receptor by these proteinases was detected by Western blot analysis. These findings suggest that P. gingivalis cysteine proteinases may alter the cytokine network at the point of infection through the cleavage of IFN-γ. Degradation of IFN-γ could have important consequences for the recruitment and activation of leukocytes and therefore may contribute significantly to the destruction of the periodontal attachment.